Analysis of The Implications of The Use of Firearms by Immigration Officers in Law Enforcement According to The Act Number 63 Year 2024 - Pradana, Erlangga Danny Rimba; Wijanarko, Ervan Fawwaaz (Polteknik Imigrasi, 2024)
Abstract. The advancement of era has made the challenges in immigration more complex. The enactment of the Law Number 63 of 2024 as the latest Immigration Law, replacing Law Number 6 of 2011 is an effort by the government to strengthen the institutional framework of the Immigration institution. One of the latest points in the law is the addition of provision 1 (one) section in Article 3 into 4 (four) sections regarding the use of firearms by certain Immigration officer in carrying out immigration functions to maintain national security and law enforcement. This research uses a normative-empirical approach to analyze the impact of the new policy on work safety, the effectiveness of law enforcement, and the challenges that arise in its implementation. Since the regulation on the use of firearms has just been issued, strict regulations are needed for Immigration officials to avoid potential misuse.